The impact of geopolitical risks on tourism - Marius-Cristian Neacşu; Silviu Neguţ; Gheorghe Vlăsceanu (Amfiteatru Economic Journal, 2018)
This study captures the new context of contemporary tourism activity developing within the emergence of geopolitical risks. Tourism, an expression of freedom, has become more and more conditioned by geopolitics, thus by power manifestation in the sense of freedom being limited. Therefore, this study is an exploratory analysis meant to identify the impact of geopolitical risks on tourism activities.
Keywords: L83; F51; Z32; 330; geopolitics; geopolitical risks; global terrorism; tourism